Development of Wee Gemas Learning Media Based on Student Learning Styles for Physics Subjects (Universitas Negeri Surabaya, 2021)
Wee Gemas (Golden Generation Educational Website) is a learning media in the form of web-based teaching materials that are integrated with student learning styles. This study aims to determine the effectiveness of Wee Gemas in learning physics in high school. It is expected to be able to support student learning independently in understanding Physics learning can make students more independent in understanding Physics lessons. The method used is R&D development, which consists of several stages, namely potential and problems, information gathering, product design, design validation, design improvement, first product testing, product revision, and second product testing. The results of media validation on aspects of learning, material, and media each obtained a validity percentage of 97.27%; 87.5%; and 94.77%. In trials that were tested in small groups obtained very good results in their category. In the final pre-test and post-test involving 32 students of SMA Hangtuah Sidoarjo with the enough effective category. It can conclude that Wee Gemas learning media is said to be feasible with the predicate very good and useful for use, especially during the Covid-19 pandemic where students must learn from home. Access to learning resources that are following student learning styles is very much needed by students when teachers are not fully able to explain the physics learning during online meetings with students. Keywords: Students; Website; Learning style; Learning media. Wee Gemas (Situs Edukasi Generasi Emas) merupakan media pembelajaran berupa bahan ajar berbasis web yang terintegrasi dengan gaya belajar siswa. Penelitian ini bertujuan untuk mengetahui keefektifan Wee Gemas dalam pembelajaran fisika di SMA. Diharapkan dapat mendukung pembelajaran siswa secara mandiri dalam memahami pembelajaran Fisika dapat menjadikan siswa lebih mandiri dalam memahami pelajaran Fisika. Metode yang digunakan adalah pengembangan R&D, yang terdiri dari beberapa tahapan yaitu potensi dan masalah, pengumpulan informasi, desain produk, validasi desain, perbaikan desain, pengujian produk pertama, revisi produk, dan pengujian produk kedua. Hasil validasi media pada aspek pembelajaran, materi, dan media masing-masing diperoleh persentase validitas sebesar 97,27%; 87,5%; dan 94,77%. Pada uji coba yang diujikan pada kelompok kecil diperoleh hasil yang sangat baik dalam kategorinya. Pada pre-test dan post-test akhir melibatkan 32 siswa SMA Hangtuah Sidoarjo dengan kategori cukup efektif. Dapat disimpulkan bahwa media pembelajaran Wee Gemas dikatakan layak dengan predikat sangat baik dan bermanfaat untuk digunakan terutama pada masa pandemi Covid-19 dimana siswa harus belajar dari rumah. Akses sumber belajar yang mengikuti gaya belajar siswa sangat dibutuhkan oleh siswa ketika guru tidak sepenuhnya mampu menjelaskan pembelajaran fisika pada saat pertemuan online dengan siswa. Kata kunci: Mahasiswa; Situs web; Gaya belajar; media pembelajaran.